Радіологічні дослідження мінеральних вод Трускавецького родовища - Івасівка, С.В.; Бубняк, А.Б.; Дацько, О.Р.; Полюжин, І.П. (Медична гідрологія та реабілітація, 2004)
Согласно результатам радиологических исследовании, проведенных методами β- и γ- энергетической спектрометрии, минеральные воды Трускавецкого месторождения можно сгруппировать в два различных типа вод - пресные, в том числе Нафтуся, где присутствует радий-226, и россолы, которые содержат калий, идентифицированный по гамма-излучению изотопа калий-40. Содержание калия в исследованных водах определялось методом атомно-эмиссионого спектрального анализа с пламенным источником возбуждения. На формирование россолов влияют геологические пласты Стебницкого полиминерального месторождения. Исследованные минеральные воды 14 скважин Трускавецкого месторождения соответствуют действующим нормам по радиологическим показателям. The mineral waters from Truskavets deposit can be grouped into two different water types as following – fresh waters including Naftusya kind, in which Radium-226 was identified, and next group such as brines, in which Potassium was identified by γ-radiation of Potassium-40 isotope, according to the results of radiological investigations carried out by means of β- and γ- energy spectrometry. In waters investigated the Potassium content was found by means of atomic-emission spectral analysis with flame exiting source. The geological layers of Stebnik polymineral deposit influence on the brines formation. The minerals waters investigated from 14 wells of Truskavets deposit correspond to the requirements of the radiological standards.